2019
DOI: 10.1021/acsomega.9b00420
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature (400 °C) Synthesis of Multilayer Graphene by Metal-Assisted Sputtering Deposition

Abstract: Low-temperature synthesis of multilayer graphene (MLG) is essential for combining advanced electronic devices with carbon materials. We investigated the vapor-phase synthesis of MLG by sputtering deposition of C atoms on metal-coated insulators. Ni, Co, and Fe catalysts, which have high C solid solubility, enabled us to form MLG at 400 °C. The domain size and surface coverage of MLG were determined by the supplied amount of C atoms and the thickness of the metal layer associated with the solid solution amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…To improve efficiency these factors are essential for research into high power and energy as well as overall super-capacity improvements [186,187]. Around most of these 3D graphene buildings showed outstanding electrochemical behavior for energy storage and other functional properties such as physical and catalytic [188]. Innumerable production techniques for preparing supercapacitor electrodes based on 3D graphene have been verified.…”
Section: Transition Metal Oxides-graphene Compositesmentioning
confidence: 98%
“…To improve efficiency these factors are essential for research into high power and energy as well as overall super-capacity improvements [186,187]. Around most of these 3D graphene buildings showed outstanding electrochemical behavior for energy storage and other functional properties such as physical and catalytic [188]. Innumerable production techniques for preparing supercapacitor electrodes based on 3D graphene have been verified.…”
Section: Transition Metal Oxides-graphene Compositesmentioning
confidence: 98%
“…Most studies on the application of CdS films as buffer layers explain the physical properties at substrate temperatures below 300 °C. However, the characteristics of the devices may be determined based on the characteristics of CdS films exhibited at substrate temperatures above 300 °C when the CdS film is applied as a junction layer for electronic devices other than the buffer layer of solar cells [ 16 , 17 , 18 ]. Therefore, further research on the physical properties of CdS thin films over a wide range of substrate temperatures is required.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Nakajima et al realized the preparation of multilayer graphene at 400 °C on the Ni surface by using amorphous carbon sputtered on an Ni surface as a carbon resource. 48 Moreover, the proper size and thickness of droplet Ni is beneficial to the synthesis of monolayer graphene domains. 49 It was also found that graphene growth could break through the limitation of edges of Ni droplets, forming a continuous monolayer graphene film over discontinuous Ni droplets.…”
Section: Surface Engineering Of Catalytic Substrates For Graphene Growthmentioning
confidence: 99%